Seasonal variations of soil bacterial and fungal communities in a subtropical Eucalyptus plantation and their responses to throughfall reduction - Lin, Yubiao; Yang, Ling; Chen, Zetao; Gao, Yaqian; Kong, Jiejun; He, Qian; Su, Yan; Li, Jiyue; Qiu, Quan (Frontiers in Microbiology, 2023)
Climatic change causes obvious seasonal meteorological drought in Southern China, yet comprehensive situ studies on drought effects in Eucalyptus plantations have rarely been conducted. Here, we conducted a 50% throughfall reduction (TR) experiment to investigate the seasonal variations of soil microbial communities and functions in a subtropical Eucalyptus plantation and their responses to TR treatment. We collected soil samples from control (CK) and TR plots for high-throughput sequencing analysis in the dry and rainy seasons. Results showed that TR treatment significantly reduced soil water content. Fungal alpha diversity decreased in the rainy season while bacterial alpha diversity did not change significantly between dry and rainy seasons. Moreover, bacterial networks were more affected by seasonal variations than fungal networks. Redundancy analysis showed that alkali hydrolyzed nitrogen (AHN) and total organic carbon (TOC) were the main environmental factors affecting bacterial and fungal communities. By functional prediction, we found that the expression of soil bacterial metabolic functions and symbiotic fungi decreased in the rainy season. In conclusion, our results show that seasonal variations have a stronger effect on soil microbial community composition, diversity, and function than the TR treatment. These findings could be used to develop management practices for subtropical Eucalyptus plantations and help maintain soil microbial diversity to sustain long-term ecosystem function and services in response to future changes in precipitation patterns.